Increasing Students' Living Results in Class 1 Through Make A Match Learning Model - Hartatik, Hartatik (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research was carried out with the aim of describing the increase in learning outcomes of harmonious living material after being given learning with the Make A Match model in grade 1 odd semester students of SD Negeri 2 Girimarto. This research is a Classroom Action Research (CAR) which includes several stages, namely: planning, implementing actions, observing, and reflecting which are always carried out in each cycle. Data collection techniques in the form of observation documents and interviews. The results of the study with the average student learning outcomes initially 66 then increased to 75.33 in the first cycle and 80.66 in the second cycle. And with the percentage of student learning completeness initially 20% then increased to 53.33% in the first cycle and 86.66% in the second cycle. Thus, it can be concluded that the use of the Make A Match learning model is more effective in improving the learning outcomes of harmonious living material for Civics Class 1 odd semester students at SD Negeri 2 Girimarto for the 2020/2021 academic year, Girimarto District, Wonogiri Regency.